2013
DOI: 10.2144/000114055
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Intact Intestinal Epithelium from Mesenchyme

Abstract: Current protocols for separating adult intestinal epithelial cells from the underlying muscular and mesenchymal tissues typically involve extended incubations, harsh mechanical treatment, and exposure to either proteases or chelating agents. The drawbacks of these approaches include fragmentation, contamination with other cell types, reduced viability, and under-representation of crypt cells. Here we describe a gentle procedure that allows harvesting of pure, fully viable sheets of murine intestinal epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…To test whether a 3‐day HFD exposure differentially regulated the gene and protein expression of key metabolic enzymes, we isolated the enterocytes with a novel and very specific method. This method allows for a fast and specific isolation of intestinal epithelial cells without the use of enzymes or EDTA and can be performed in ice cold conditions (Nik and Carlsson, ). We consistently found that 3 and 14 days of HFD feeding reduced the expression of genes related to glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether a 3‐day HFD exposure differentially regulated the gene and protein expression of key metabolic enzymes, we isolated the enterocytes with a novel and very specific method. This method allows for a fast and specific isolation of intestinal epithelial cells without the use of enzymes or EDTA and can be performed in ice cold conditions (Nik and Carlsson, ). We consistently found that 3 and 14 days of HFD feeding reduced the expression of genes related to glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic epithelium were isolated using Cell Recovery Solution (Corning) as described (Nik and Carlsson, 2013). Briefly, colons were removed and flushed several times with ice-cold PBS.…”
Section: Star Methodsmentioning
confidence: 99%
“…To obtain homogenate from GI tissue, small intestinal epithelium was isolated from mesenchyme following a protocol after Nik and Carlsson70. In brief, small intestine was cut into 4–5 cm long pieces.…”
Section: Methodsmentioning
confidence: 99%